2018
DOI: 10.1177/1753944718792420
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of elderly out-of-hospital cardiac arrest survivors as compared with their younger counterparts and the general population

Abstract: Background:Over the past decade, prehospital and in-hospital treatment for out-of-hospital cardiac arrest (OHCA) has improved considerably. There are sparse data on the long-term outcome, especially in elderly patients. We studied whether elderly patients benefit to the same extent compared with younger patients and at long-term follow up as compared with the general population.Methods:Between 2001 and 2010, data from all patients presented to our hospital after OHCA were recorded. Elderly patients (⩾75 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…As long term prognosis of OHCA survivors is essentially determined by their neurological status, an early assessment is crucial to predict an unfavorable course with poor neurological outcome [ 22 ]. Anoxic brain injury is the leading neurological cause of death following OHCA rather than brain death, which accounts for only about 10% of causes [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…As long term prognosis of OHCA survivors is essentially determined by their neurological status, an early assessment is crucial to predict an unfavorable course with poor neurological outcome [ 22 ]. Anoxic brain injury is the leading neurological cause of death following OHCA rather than brain death, which accounts for only about 10% of causes [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A survival rate that corresponds to that of the general population has been reported in elderly patients surviving to hospital discharge after out-of-hospital cardiac arrest (OHCA), whereas elderly patients with severe traumatic brain injury are characterised by overmortality. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, several studies and meta-analyses have shown that age negatively affects post-CA mortality [26]. Long-term survival among elderly CA patients is generally lower than that among younger age groups in the case of OHCA [27,28].…”
Section: Discussionmentioning
confidence: 99%